Laser CVD growth of graphene/SiC/Si nano-matrix heterostructure with improved electrochemical capacitance and cycle stability. (30th April 2021) - Liu, Zhizhuang; Cai, Yilun; Tu, Rong; Xu, Qingfang; Hu, Mingwei; Wang, Chongjie; Sun, Qingyun; Li, Bao-Wen; Zhang, Song; Wang, Chuanbin; Goto, Takashi; Zhang, Lianmeng
Abstract : Si-based micro-supercapacitors are considered to be promising in energy storage due to their compatibility to modern electronics and high energy densities. However, the capacitance and cycle stability of the electrode remains to be further improved. In this work, we fabricated high-crystalline graphene/SiC (G/SiC) nano-matrix on the surface of planar Si and Si nanowires (SiNWs) array by laser chemical vapor deposition. The surface of SiNWs was fully covered with the G/SiC passivation layers, which composed of highly <001>−orientated 3C–SiC with graphene distributed in the films and the outermost layer. Compared to the SiNWs and planar G/SiC/Si structures, the G/SiC/SiNWs nano-matrix exhibited a low charge transfer resistance of 3.1 Ω, and a high areal capacitance value of ∼3.2 mF/cm 2 achieved at a CV scan rate of 50 mV/s, nearly 10 times and 75 times higher than those of SiNWs and G/SiC/Si, respectively. The capacitance of the G/SiC/SiNWs nano-matrix was increased by 115% after 10, 000 cyclic voltammetry cycles at 100 mV/s, showing excellent cyclic stability. This type of G/SiC/SiNWs nano-matrix heterostructure electrode paves the way for Si-based electrochemical applications. Graphical abstract: Image 1